Women on the executive and supervisory boards of large companies: The upward trend of recent years has largely stalled - Arianna Antezza; Alina Meiner; Katharina Wrohlich (DIW Weekly Report, 2026)
The proportion of women on the executive and supervisory boards of Germany's largest private companies has risen considerably since data collection for the DIW Women Executives Barometer began 20 years ago. While it was just over one percent on the executive boards of Germany's 200 highest-revenue companies in 2006, it is now around 19 percent. The proportion of women on supervisory boards in the top 200 group has risen from just under 8 percent to around 34 percent since 2006. The trend is very similar in the other corporate groups surveyed, including DAX companies as well as the country's largest banks and insurance companies. However, the latest Women Executives Barometer is a downer in this regard: in late fall 2025, the proportion of women on the executive boards of almost all corporate groups surveyed had stagnated compared to 2024; in some places it has even declined. One exception is the financial sector, where the proportion of women on executive boards has continued to increase. It is still too early to assess whether this development is just a slight dip in the long-term positive trend or whether it marks the beginning of a longer phase of stagnation or even decline in the proportion of women in management positions.
Keywords: J16; J59; J78; L21; L32; M14; M5; 330; corporate boards; board composition; boards of directors; board diversity; women directors; executive directors; gender equality; gender quota; Germany